Hubungan Kepatuhan Minum Obat Hipertensi dengan Kualitas Hidup Lasia di Wilayah Kerja Puskesmas Sei Langkai Kota Batam - Novrizal, Yogi; Alba, Afif D. (Jurnal Siti Rufaidah, 2025)
Hypertension is a common health problem in the elderly that can affect quality of life. Hypertension in Batam city is a non-communicable disease that ranks 2 and with a percentage of 30.9%. The World Health Organization (WHO) said that there are 50 70% of hypertensive patients who do not comply with prescribed medications. Compliance with taking antihypertensive drugs is important to maintain blood pressure stability. Non-compliance in using antihypertensive drugs is one of the risk factors for increasing morbidity and uncontrolled hypertension events that can worsen the quality of life of hypertensive patients. This study aims to find out "The Relationship between Compliance with Taking Hypertension Medication and the Quality of Life of the Elderly in the Working Area of the Sei Lengkai Health Center in 2024". The research design used in this study is cross sectional. Data collection uses secondary data with the population of hypertension patients in Batam city in 2023 and primary data, namely a questionnaire on adherence to taking hypertension medication and quality of life for the elderly. Sampling was done using a purposive sampling technique with a total of 93 elderly people. The measuring tools in this study are the Morisky Medication Adherence Scale (MMAS-8) and WHOQOL-BREF questionnaires. Based on the results of the analysis, it is known that the p value is 0.003, this states that there is a relationship between compliance with taking hypertension medication and the quality of life of the elderly in the Sei Langkai Health Center Work Area in 2024. The conclusion of this study is that adherence to taking antihypertensive medication is positively related to the quality of life of the elderly, so efforts are needed to increase medication adherence to support a better quality of life in the elderly. It is hoped that families and health workers will provide support and education to the elderly to maintain compliance in taking their medication to improve their quality of life